Interview with Shariah supervisors in Malaysian Islamic banks - Uddin, Mohi; Hossin, M.M Ismail; Islam, Mohd Aminul (Scholars Middle East Publishers, 2017)
Shariah Supervisors plays a significant role in the Islamic banking system, and it has a significant impact on their performance as well as stability. The study focused on the banking system and on the Shariah Supervisors as a significant element of it. The study aims at showing the impact of the Shariah Supervisors on the Islamic bank stability. It also exposes the significance to be Independent department in the completion of its decisions. The study concluded that Shariah Supervisors Interview and their responds are significant in the Islamic credit card, compliance of Shari‟ah requirement. The interfering of decision-making and as well as Supervisors are adversely affect for the Islamic credit card in Malaysia.